2003
DOI: 10.1002/jcb.10540
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐dihydroxyvitamin D3 inhibits ultraviolet B‐induced apoptosis, Jun kinase activation, and interleukin‐6 production in primary human keratinocytes

Abstract: We investigated the capacity of 1,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)] to protect human keratinocytes against the hazardous effects of ultraviolet B (UVB)-irradiation, recognized as the most important etiological factor in the development of skin cancer. Cytoprotective effects of 1,25(OH)(2)D(3) on UVB-irradiated keratinocytes were seen morphologically and quantified using a colorimetric survival assay. Moreover, 1,25(OH)(2)D(3) suppressed UVB-induced apoptotic cell death. An ELISA, detecting DNA-fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
130
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 49 publications
8
130
1
2
Order By: Relevance
“…Suppression of UV-stimulated IL-6 production by 1,25D was previously shown in keratinocytes (27) and we suspected that similar activity could be mediated by MKP5 in normal prostatic epithelial cells. Using MKP5 siRNA, we showed that 1,25D inhibited UV-stimulated p38 activity and IL-6 production in a MKP5-dependent manner in E-PZ cells.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Suppression of UV-stimulated IL-6 production by 1,25D was previously shown in keratinocytes (27) and we suspected that similar activity could be mediated by MKP5 in normal prostatic epithelial cells. Using MKP5 siRNA, we showed that 1,25D inhibited UV-stimulated p38 activity and IL-6 production in a MKP5-dependent manner in E-PZ cells.…”
Section: Discussionsupporting
confidence: 67%
“…Published studies have shown that 1,25D inhibits UVinduced IL-6 production in keratinocytes; however, no mechanism has been proposed (27). IL-6 overexpression has been strongly associated with PCa progression and, therefore, inhibition of IL-6 may play an important role in PCa prevention.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-apoptotic actions of 1,25-(OH) 2 D 3 have been described in keratinocytes (45,46), osteoblasts (47), lymphocytes (48), thyrocytes (49), and osteosarcoma cells (50). The functions are consistent with the positive physiological role of 1,25-(OH) 2 D 3 in regulating the survival and differentiation of cells of skin, bone, and the immune system.…”
Section: Discussionmentioning
confidence: 65%
“…1,25D3 inhibits UV B-induced apoptosis through the blockage of cytochrome c release from mitochondria in primary human keratinocytes (40). 1,25D3 upregulates Bcl-2 protein expression in normal human thyrocytes and protects them from apoptotic cell death (41).…”
Section: Discussionmentioning
confidence: 99%